Force Steadiness during Submaximal Isometric Plantar and Dorsiflexion in Resistance Training: Experienced vs Non-experienced Individuals - Konstantinos Salonikidis; Konstantinos Papageorgiou; Anastasios Meliadis; Fotini Arabatzi (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
The purpose of this study was to determine differences in force steadiness during submaximal plantar flexion (PF) and dorsiflexion (DF) of the dominant leg between individuals experienced and not experienced in resistance training. Forty males aged 18-32 were divided in two groups based on their experience in resistance training (experienced - not experienced). Evaluation of maximal voluntary isometric force was carried out on a Humac-Norm isokinetic dynamometer. The measurement of the maximal voluntary contraction (MVC) was measured in 3 isometric attempts. Then, the stability measurement of 10%, 30%, 50% and 70% of the MVC was assessed. The duration of the isometric contraction was 10 seconds but only 6 seconds were analyzed. T-test for independent samples and ANOVA was applied for the statistical analysis. The results showed that the individuals with more experience in resistance training presented a significantly higher MVC and force steadiness of the plantar and dorsiflexors muscles, compared with the individuals with less experience (p < 0.05). In conclusion, the years of practice with resistance training appear to have a beneficial effect on force steadiness.